Investigation of readily available polymer for optical propagation - 274823 Khairun Neeza Ramly (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Telekomunikasi)) - Universiti Teknologi Malaysia, 2007